The termination of tribute in the Spanish Philippines in 1884 the treasury and Spanish sovereignty - Aguilar, Filomeno V., Jr. (2023)
Why did Spain abolish tribute in 1884 although it was a huge generator of revenue? The answer is contextualized in terms of Spain's search for a tax that would allow terminating the tobacco monopoly, subsidizing Madrid, and funding the modernization and retention of the Philippines under Spain's sovereignty. Spanish officialdom regarded the race-based tribute system as anomalous, antiquated, and constrained in expanding the tax base. In 1885 Spain instituted the cedulas personales, which charged tax rates based on economic capacity. Did Spain attain its aims? Fiscally, yes; but its gradualist approach to forestall resistance did not prevent disaffection and revolution.
Keywords: Philippines -- History -- Spanish regime, 1521-1898; Taxation -- Law and legislation; Tobacco monopoly; Tobacco -- Taxation -- Law and legislation; Taxation -- Social aspects